Ambidexteritg leadership behaviors in organizational excellence Comparative : applied research in the two public companies, Al-Zawraa and the electrical and electronic industries (Journal of Accounting and Financial Studies ( JAFS ), 2022)
Business organizations strive to reach organizational excellence, in instruction to maintain their position in the market, so the research started from the problem of the weakness of the senior leaders in the two companies investigated in the management and sustainability of work, as well as their inability to face challenges that could affect the work of the two companies in the future, especially the lack of organizational of the future and the prediction of those events, so the two companies seek to explore and invest opportunities to achieve organizational excellence. The research aims to know the role of Ambidexterity  leadership behaviors in organizational excellence in my company .and create ideas that will achieve organizational excellence in the two companies. The researcher adopted the comparative analytical descriptive approach in completing the research by targeting an intentional sample of the senior management levels (overall manager, assistant overall manager, department head, separation official), as the size of the community reached (85) managers within the administrative competencies, and the questionnaire form was distributed , so that the number of final forms valid for analysis is (67) responding to the two companies. The most important results were the existence. Of a direct correlation with. A significant significance between the dimensions of the study variables (Ambidexterity  leadership behaviors, organizational excellence) for the two companies, the study also found a significant impact of Ambidexterity  leadership behavior in its dimensions on organizational excellence in its dimensions for the two companies.